A Treatment Option for Symptomatic Chronic Complete Internal Carotid Artery Occlusion: Hybrid Surgery - Yang, Yunna; Liu, Xingju; Wang, Rong; Zhang, Yan; Zhang, Dong; Zhao, Jizong (Frontiers in Neuroscience, 2020)
Background Internal carotid artery occlusion (ICAO) is a relatively uncommon but important cause of transient ischemic attack and cerebral infarction. The majority of cases of symptomatic ICAO requires surgical treatment. In this study we performed an investigation of the efficacy and safety of hybrid surgery which is a surgical method for symptomatic chronic complete ICAO. Methods Fifty-five patients with symptomatic chronic ICAO treated by hybrid surgery from 2016 to 2019 were included. We recorded and analyzed the patients’ clinical characteristics, angiographic data, recanalization rate, complications, and outcomes. Catheter angiography or computed tomography angiography was used to assess the patency of the recanalized ICA during follow-up. Results The total success rate of recanalization was 78.2% (43/55). The occlusions were significantly shorter in the success than failure group (5.40±1.50 vs. 7.56±0.99 cm, respectively; P<0.001). The median duration of ICA occlusion was significantly shorter in the success than failure group (90 vs. 200 days, respectively). The success rates of distal ICA recanalization at the petrous segment or below, cavernous segment, and clinoid segment or above were 100%, 33.3%, and 14.3%, respectively (P<0.001). Multivariate analysis showed that the level of distal ICA reconstitution was the only factor affecting the recanalization success rate. Periprocedural complications included hyperperfusion syndrome (n=1) and laryngeal nerve injury (n=1). ICA reocclusion occurred in one patient (2.3%). Significant postoperative improvement in symptoms was observed in the success group, with a median modified Rankin scale score of 0 at the 3-month follow-up compared with before recanalization (median, 1) (P＜0.001). Conclusion Hybrid surgery is safe and effective for patients with symptomatic chronic complete ICAO. The level of distal ICA reconstitution is a predictor of successful recanalization in hybrid operations.